Analysis of select Newspapers’ reportage of the 2022 Abuja-Kaduna Terrorist Train attack - Inioluwa Oladele, Victor; Mustapha Asekhamhe, Okpokpo; Ubaka Ofunne, Anthony; Phoebe Oloyede, Oluwaseun (COMMICAST, 2025)
Insecurity remains a pressing national concern in Nigeria, yet the media is often criticized for not fully performing its watchdog role in sensitizing the public and holding institutions accountable. This study examined newspapers’ reportage of the 2022 Abuja-Kaduna terrorist train attack between March and November 2022. The Nigerian Tribune and The Punch were selected, yielding 492 editions from which a sample of 217 was drawn using the Krejcie and Morgan sample size calculator. Purposive and simple random sampling techniques were employed, and data were generated through content analysis. Straight news stories, features, illustrations, and special reports served as the main units of analysis, while Critical Theory of Society and Priming Theory provided theoretical grounding. Findings revealed that coverage of the Abuja-Kaduna attack was initially frequent but gradually declined over time. Furthermore, the two newspapers accorded low prominence to the incident, with most reports placed on inside pages rather than front pages. The dominant thematic framing emphasized rescue efforts, while other critical dimensions such as accountability and root causes of insecurity received limited attention. The study concludes that the prominence and frequency of reportage were disproportionately low compared to the gravity of the terrorist attack. This research contributes to media and security scholarship by highlighting gaps in Nigerian newspapers’ coverage of terrorism, particularly in terms of agenda-setting and priming functions. It underscores the need for continuous, balanced, and prominent reportage of security issues to promote public awareness, accountability, and resilience in addressing insecurity in Nigeria.